The Impact of Financial Technology Usage, Financial Inclusion, and Financial Behavior on SME Performance - Nisya Puspita Safitri; Stelly Morasa; Hendry Rumengan (Malaqbi Publisher, 2026)
Small and medium enterprises (SMEs) play a crucial role in economic growth, employment generation, and innovation in many countries. However, many SMEs still face challenges related to limited access to financial services, inefficient financial management, and low adoption of digital financial technologies. This study aims to examine the impact of financial technology usage, financial inclusion, and financial behavior on SME performance. A quantitative research approach was employed using primary data collected from 150 SME owners and managers through structured questionnaires. The data were analyzed using descriptive statistics, reliability and validity tests, correlation analysis, and multiple regression analysis. The results show that financial technology usage has a positive and significant effect on SME performance, indicating that the adoption of digital financial services can improve operational efficiency and financial accessibility for SMEs. Financial inclusion also has a significant positive influence on SME performance, suggesting that greater access to financial products and services enables SMEs to obtain capital, manage financial risks, and support business expansion. Furthermore, financial behavior was found to have the strongest positive effect on SME performance, highlighting the importance of responsible financial management practices such as budgeting, financial planning, and effective resource allocation. These findings suggest that the combination of digital financial technology adoption, expanded financial inclusion, and improved financial behavior plays an important role in enhancing SME competitiveness and sustainability. Therefore, policymakers, financial institutions, and SME development programs should encourage fintech adoption, expand financial inclusion initiatives, and improve financial literacy among SME owners to support sustainable SME growth in the digital economy.